Effects of electrode size and placement on comfort and efficiency during low-intensity neuromuscular electrical stimulation of quadriceps, hamstrings and gluteal muscles - J. Flodin; R. Juthberg; P. W. Ackermann (BMC, 2022)
Abstract Background Neuromuscular electrical stimulation (NMES) may prevent muscle atrophy, accelerate rehabilitation and enhance blood circulation. Yet, one major drawback is that patient compliance is impeded by the discomfort experienced. It is well-known that the size and placement of electrodes affect the comfort and effect during high-intensity NMES. However, during low-intensity NMES the effects of electrode size/placement are mostly unknown. Therefore, the purpose of this study was to investigate how electrode size and pragmatic placement affect comfort and effect of low-intensity NMES in the thigh and gluteal muscles. Methods On 15 healthy participants, NMES-intensity (mA) was increased until visible muscle contraction, applied with three electrode sizes (2 × 2 cm, 5 × 5 cm, 5 × 9 cm), in three different configurations on quadriceps and hamstrings (short-transverse (ST), long-transverse (LT), longitudinal (L)) and two configurations on gluteus maximus (short-longitudinal (SL) and long-longitudinal (LL)). Current-density (mA/cm2) required for contraction was calculated for each electrode size. Comfort was assessed with a numerical rating scale (NRS, 0-10). Significance was set to p < 0.05 and values were expressed as median (inter-quartile range). Results On quadriceps the LT-placement exhibited significantly better comfort and lower current intensity than the ST- and L-placements. On hamstrings the L-placement resulted in the best comfort together with the lowest intensity. On gluteus maximus the LL-placement demonstrated better comfort and required less intensity than SL-placement. On all muscles, the 5 × 5 cm and 5 × 9 cm electrodes were significantly more comfortable and required less current-density for contraction than the 2 × 2 cm electrode. Conclusion During low-intensity NMES-treatment, an optimized electrode size and practical placement on each individual muscle of quadriceps, hamstrings and gluteals is crucial for comfort and intensity needed for muscle contraction.